The Impact of Infrastructure Management and Information Systems on Teacher’s Learning Innovation in the Digital Transformation of Schools - Ayu Sri Wahyuni; Nur Ahyani; Darwin Effendi (Yayasan Sembilan Pemuda Indonesia, 2026)
Digital transformation in education requires effective infrastructure and information systems to foster teacher innovation. This study examines the influence of infrastructure management and information systems on teacher learning innovation in public junior high schools in Palembang, Indonesia. This research uses a descriptive method with a quantitative approach. A quantitative survey was administered to 88 teachers. The research instrument was a Likert scale questionnaire which had been tested for validity and reliability. Results from multiple regression analysis revealed that both infrastructure management (p = 0.031) and information systems (p < 0.001) significantly predicted teacher learning innovation, collectively explaining 42.8% of the variance. These findings underscore the importance of infrastructure and information system management, in this case integrated digital resources, in supporting pedagogical innovation during the digital transformation of education.